Influence of patient mispositioning on SAR distribution and simulated temperature in regional deep hyperthermia. (22nd May 2017) - Aklan, Bassim; Gierse, Pia; Hartmann, Josefin; Ott, Oliver J; Fietkau, Rainer; Bert, Christoph
Abstract: Patient positioning plays an important role in regional deep hyperthermia to obtain a successful hyperthermia treatment. In this study, the influence of possible patient mispositioning was systematically assessed on specific absorption rate (SAR) and temperature distribution. With a finite difference time domain approach, the SAR and temperature distributions were predicted for six patients at 312 positions. Patient displacements and rotations as well as the combination of both were considered inside the Sigma-Eye applicator. Position sensitivity is assessed for hyperthermia treatment planning -guided steering, which relies on model-based optimization of the SAR and temperature distribution. The evaluation of the patient mispositioning was done with and without optimization. The evaluation without optimization was made by creating a treatment plan for the patient reference position in the center of the applicator and applied for all other positions, while the evaluation with optimization was based on creating an individual plan for each position. The parameter T90 was used for the temperature evaluation, which was defined as the temperature that covers 90% of the gross tumor volume (GTV). Furthermore, the hotspot tumor quotient (HTQ) was used as a goal function to assess the quality of the SAR and temperature distribution. The T90 was shown considerably dependent on the position within the applicator. Without optimization, the T90 was clearly decreased below 40 °C by patient shifts and the combination of shifts and rotations. However, the application of optimization for each positon led to an increase of T90 in the GTV. Position inaccuracies of less than 1 cm in the X -and Y -directions and 2 cm in the Z -direction, resulted in an increase of HTQ of less than 5%, which does not significantly affect the SAR and temperature distribution. Current positioning precision is sufficient in the X (right–left)-direction, but position accuracy is required in the Y -and Z -directions.